THE INFLUENCE OF INCOME, EXPENDITURE, AND SAVINGS TN THE EFFECTIVENESS OF FINANCIAL PLANNING IN THE DIGITAL ERA: A SURVEY OF THE SANDWICH GENERATION AMONG PRIVATE SECTOR EMPLOYEES IN MEDAN - Manurung, Nancy Cecilia; Panjaitan, Raya; Sitorus, Sunday Ade; SUNDAY ADE SITORUS (SULTANIST: Jurnal Manajemen dan Keuangan, 2025)
The sandwich generation refers to working-age individuals who simultaneously bear financial responsibilities for both their aging parents and their children. This phenomenon is increasingly prevalent in Indonesia, particularly among private sector employees, due to rising costs of living, education, and healthcare. Low levels of financial literacy further exacerbate the challenges, making effective financial planning increasingly urgent. This study aims to analyze the influence of income, expenses, and savings on financial planning effectiveness among the sandwich generation in Medan City. A quantitative approach was applied through the distribution of questionnaires to respondents aged 23–50 who qualified as part of this demographic. The results indicate that income and savings have a positive and significant effect on financial planning effectiveness, whereas expenses show no significant influence. These findings emphasize the importance of income management and saving habits in achieving household financial resilience. The study recommends strengthening financial literacy and leveraging digital financial technologies as strategies to enhance long-term economic stability for the sandwich generation.